KARAKTERISTIK, MOTIVASI DAN KEPUASAN WISATAWAN NUSANTARA YANG BERKUNJUNG KE DAYA TARIK WISATA CITY TOUR DENPASAR - Tenouye, Pius; Suardana, I Wayan; Susrami Dewi, Ni Gusti Ayu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 5 No 1 (2017): Jurnal IPTA (July 2017), 2017)
This study aims to determine the characteristics, motivation and satisfaction of tourists who visit the tourist attraction city tour Denpasar. Research methods include: observation, questionnaires to 100 tourists, literature study and documentation and descriptive qualitative as the analysis techniques. The results showed that the characteristics of tourists dominated 81% aged 15-30 years, 60% male, 79% are not married, university level education 71%, 77% students, 56% of the island of Java, resources through friends / family 36 %, 62% ground transportation, hotel accommodations as a means of 65%, frequency of visit to Bali 2-3 times 75%, 45% choose to visit, type of visit 65%, 65% of people who had been invited, organizers of 75%. Furthermore, intrinsic motivation tourists dominated by indicators want to know the Balinese art with scale score of 4.21 (strong), while extrinsic motivation is dominated indicators admission fee affordable fascination with score of 4.20 (strong). In general, tourists are satisfied with the tourist attraction, and the indicator that dominates is the physical aspect of the form of security with score of 4.33 (very satisfied) and non-physical aspects of the hospitality and courtesy clerk with score of 4.97 (very satisfied). Through this research is expected the municipality, manager of a tourist attraction can improve the quality and attractiveness of city tour service in accordance with the characteristics, motivation and satisfaction of tourists so the frequency and the number of tourist arrivals increased evenly.
Keywords: Characteristic, Motivation, Satisfaction, Domestic Tourist, City Tour Denpasar